PENERAPAN STRATEGI PEMBELAJARAN KOOPERATIF WORD SQUARE UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN TATA NAMA SENYAWA DI KELAS X MIA SMAN 4 PEKANBARU - ', Nirmalasari; Rery, Radjawaly Usman; ', Rini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Research on the application of cooperative learning strategy word square has been done to know the improvement student’s achievement on the topic of compound’s chemical nomenclatur in class X MIA SMAN 4 Pekanbaru. This from of research is quasi-experiment research with randomized control group pretest-posttest design. The sample consisted of two classes, namely class X MIA 4 as the experimental class and homogeneity test. Experiment class that ware subjected of cooperative learning strategy word square, while the control class is a class that untreated cooperative learning strategy word square . Based on the results obtained tvalue final calculation is 3,36 greater than ttable is 1,66. It can be concluded that the application of cooperative learning strategy word square to improve student’s achievement on the subject of compound’ chemical nomenclatur in class X MIA SMAN 4 PekanbaruKeyword: Cooperative Learning, Word Square, Learning Achievement, chemical nomenclatur